Health care utilization and cost among the elderly in Miagao, Iloilo. - Evaristo, Herlie Rubite
This paper described the health care utilization pattern and cost determined the significant factors affecting the utilization of health care services among 110 registered senior citizens from three barangays in poblacion Miagao. Data on their illness profile were gathered through personal interviews. One hundred seven participants reported having been ill during the last three months prior to interview. Out of these 107 participants, 50 sought medical care while the rest either opted for self-treatment or did nothing at all. Only 4 participants out of those who sought medical care were hospitalized. The major illnesses mentioned were cough, headache, fever, influenza, arthritis, back pain, stomachache, high blood pressure, asthma and gastritis. The facilities frequently visited by those who sought medical care were the Rural Health Unit (RHU), private clinics and private hospitals. More than the majority of the participants were attended by private doctors in private hospitals and clinics. Results of the Logistic Regression showed that the significant factors affecting the elders' health care utilization include the monetary costs incurred during the consultation or hospitlaization and if they have adult children who live with them. Higher monetary costs during consultation or hospitalization and presence of adult children both decrease the likelihood of elders to seek professional care. Increasing the number of health care providers would lessen the time costs by reducing the waiting time before actual consultation. It is recommended that more studies on the elderly population and their health concerns be conducted as it is among those vulnerable populations that are given less attention on health care needs. Moreover, future similar studies should have a greater number of participants to increase the variability of responses and make the results more representative of the entire population.